1996
DOI: 10.2355/isijinternational.36.1397
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Precipitates in Nb-Ti Microalloyed Steels during Solidification and Post-solidification Cooling.

Abstract: Manchester. M1 7HS, UK. A series of Nb-Ti steels containing titanium in the range 0.005 to 0,038wt"/• and nitrogen in the range 0.005 to 0.01 1 wto/• were prepared using a base composition of 0.06wto/• carbon and 0.027 wt"/• niobium.Small ingots were cooled slowly in order to simulate larger castings. Cooling was interrupted at various temperatures in the austenite phase field, either by quenching or by holding isothermally before quenching.Transmission electron microscopy (TEM) and scanning transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 1 publication
1
51
0
2
Order By: Relevance
“…The interdentritic region was usually changed to austenite grain/subgrain boundaries after the delta-to-austenite phase transformation, which was supposed to be the reason for the formation of Nb-rich precipitates at austenite grain/subgrain boundaries. The segregation ratios for Nb and Ti in interdentritic liquid pools when the solidified fraction is 5 % were estimated by Zhou and Priestner 18) to be about 8 and 3, respectively. Taking this interdentritic segregation of the solute into account in equilibrium calculations and ignoring the back diffusion of Nb and Ti during the subsequent cooling could give calculation result consistent with the measurements, as shown in Fig.…”
Section: Modeling the Precipitation In Steelsmentioning
confidence: 99%
“…The interdentritic region was usually changed to austenite grain/subgrain boundaries after the delta-to-austenite phase transformation, which was supposed to be the reason for the formation of Nb-rich precipitates at austenite grain/subgrain boundaries. The segregation ratios for Nb and Ti in interdentritic liquid pools when the solidified fraction is 5 % were estimated by Zhou and Priestner 18) to be about 8 and 3, respectively. Taking this interdentritic segregation of the solute into account in equilibrium calculations and ignoring the back diffusion of Nb and Ti during the subsequent cooling could give calculation result consistent with the measurements, as shown in Fig.…”
Section: Modeling the Precipitation In Steelsmentioning
confidence: 99%
“…Also, for cornparison, the amount Large TiN cubes in steel, in which the product of [Ti][N] was lower than the solubility product in the liquid state, has confirmed significant segregation for both Ti and N in liquid. [10,164] Furthermore, EDS analysis results from many large cuboidal carbonitrides precipitates have shown that they have a titanium-rich core surrounded by a niobium-rich skin. [164] This explains why Ti and Nb are detected at sorne grain boundary partic1es in and 14°C/wt% for Al and Si, respectively.…”
Section: Ternperatures the Solid Mns Solubility Product [%Mn][%s] Ismentioning
confidence: 99%
“…The solubility product ofthis precipitate in the liquid steel is given by. [10] [Ti] [N]= 1 05.9-16586/T This solubility limit, for the Nb-steel, is plotted in Figure 6.7 in terms of Ti versus interdentrically segregated N during the solidification. Also, for cornparison, the amount Large TiN cubes in steel, in which the product of [Ti][N] was lower than the solubility product in the liquid state, has confirmed significant segregation for both Ti and N in liquid.…”
Section: Ternperatures the Solid Mns Solubility Product [%Mn][%s] Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al have reported that in a steel similar to this composition, the transformation of d-ferrite to g-austenite takes place over this thermal range. 12) Thus, deformation at this temperature range causes an accumulation of strain in the d phase and, consequently, deformation induced transformation. This, in turn, can be responsible for the finer austenite grains observed in such specimens.…”
Section: Prior Deformation In the Proximity Of The Meltingmentioning
confidence: 99%